Accessing Improbable Foldamer Shapes with Strained Macrocycles. Issue 43 (27th May 2021) - Urushibara, Ko; Ferrand, Yann; Liu, Zhiwei; Katagiri, Kosuke; Kawahata, Masatoshi; Morvan, Estelle; D'Elia, Ryan; Pophristic, Vojislava; Tanatani, Aya; Huc, Ivan
Abstract: The alkylation of some secondary amide functions with a dimethoxybenzyl (DMB) group in oligomers of 8‐amino‐2‐quinolinecarboxylic acid destabilizes the otherwise favored helical conformations, and allows for cyclization to take place. A cyclic hexamer and a cyclic heptamer were produced in this manner. After DMB removal, X‐ray crystallography and NMR show that the macrocycles adopt strained conformations that would be improbable in noncyclic species. The high helix folding propensity of the main chain is partly expressed in these conformations, but it remains frustrated by macrocyclization. Despite being homomeric, the macrocycles possess inequivalent monomer units. Experimental and computational studies highlight specific fluxional pathways within these structures. Extensive simulated annealing molecular dynamics allow for the prediction of the conformations for larger macrocycles with up to sixteen monomers. Abstract : Frustrating folding propensity by imposing a macrocyclic structure to an otherwise helical backbone produces improbable yet stable strained molecular shapes. Both experiments and computational studies show how aromatic oligoamide foldamers constrained within a macrocycle try to fulfill their strong propensity to adopt helical conformations by forming local loops and unfolded sites that connect helical segments. Defined fluxional conformational pathways can be evidenced in such molecules.